Effects of obesity indices/GDM on the pregnancy outcomes in Chinese women: A retrospective cohort study - Song, Zhimin; Cheng, Yan; Li, Tingting; Fan, Yongfang; Zhang, Qingying; Cheng, Haidong (Frontiers in Endocrinology, 2022)
Objective: To analyze pregnancy complications and outcomes in mothers with obesity or gestational diabetes mellitus (GDM). Methods: Based on pre-pregnancy body mass index (preBMI) and abdominal circumference (AC), 15065 mothers were categorized into four and three groups by pre-pregnancy body mass index (preBMI) and abdominal circumference (AC), respectively, or divided into GDM or non-GDM groups. Logistic regression analysis was utilized to identify independent factors associated with pregnancy complications and outcomes. Results: Of the total population, 16.0% and 4.0% were predicted to develop overweight and obesity, respectively. GDM incidence rate was 12.3%. The overweight and obesity groups (preBMI ≥ 24 kg/m2) were at higher risks for GDM, hypertensive disorders of pregnancy (HDP), gestational proteinuria, postpartum hemorrhage, preterm delivery, fetal malformation or stillbirth, neonatal asphyxia, large for gestational age (LGA), shoulder dystocia, and increased cesarean section rate. Similar results were obtained with AC grouping. GDM pregnant women had higher risks of HDP, preterm delivery, small for gestational age (SGA), LGA, and increased cesarean section rate. Conclusion: People with obesity had a higher risk of adverse pregnancy outcomes. The recommended preBMI is 19.2–22.7 kg/m2. The recommended AC at 11–13+6 gestational weeks is 74.0–84.0 cm, and that value in normal preBMI is 74.0–82.0 cm.